Knowledge hiding in teachers of moral education degree programs in Pakistan: The role of servant leadership, psychological ownership, and perceived coworker support - Anwaar, Saima; Jingwei, Liu (Frontiers in Psychology, 2022)
Abstract: The purpose of this research is to examine the influence of servant leadership on teachers of moral education degree programs in Pakistan. By utilizing social learning, we propose that servant leadership and perceived coworker support can reduce the knowledge hiding through enhancing the sense of organization based psychological ownership. The findings of time-lagged and multi-source data indicate that servant leader has negative relationship with knowledge hiding. Our results also indicate that psychological ownership mediates the effects of servant leadership on knowledge hiding. Moreover, higher level of perceived coworker support enhances the sense of psychological ownership which helps to reduce knowledge hiding. This research extends strong support for the proposition that servant leaders who adopt employee-centered management approach, stressing on personal integrity and care for employees significantly effect employee attitudes and behaviors. Moreover, this study suggests that managers should show care towards their subordinates which help them to reduce negative behaviors (e.g., knowledge hiding).